Public health campaign 2025: promoting skin health awareness - Azizi, Fatin Izyani; Azlan, Saliha; Abdul Keram, Norshakila; Jahidin, Aisyah Hasyila (Faculty of Pharmacy, 2025)
The annual Public Health Campaign, endorsed by the Malaysian Pharmacy Students’ Association (MyPSA), returned this year with a focus on skin health awareness. Held at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam Campus, the campaign was jointly organised by the Society of Pharmacy Students (SOPHYS), the Faculty of Pharmacy Student Secretariat (SMF), and the Angsana College Representative Committee (JPK Angsana).